Chitosan-Based Trilayer Scaffold for Multitissue Periodontal Regeneration. (March 2018) - Varoni, E.M.; Vijayakumar, S.; Canciani, E.; Cochis, A.; De Nardo, L.; Lodi, G.; Rimondini, L.; Cerruti, M.
Periodontal regeneration is still a challenge for periodontists and tissue engineers, as it requires the simultaneous restoration of different tissues—namely, cementum, gingiva, bone, and periodontal ligament (PDL). Here, we synthetized a chitosan (CH)–based trilayer porous scaffold to achieve periodontal regeneration driven by multitissue simultaneous healing. We produced 2 porous compartments for bone and gingiva regeneration by cross-linking with genipin either medium molecular weight (MMW) or low molecular weight (LMW) CH and freeze-drying the resulting scaffolds. We synthetized a third compartment for PDL regeneration by CH electrochemical deposition; this allowed us to produce highly oriented microchannels of about 450-µm diameter intended to drive PDL fiber growth toward the dental root. In vitro characterization showed rapid equilibrium water content for MMW-CH and LMW-CH compartments (equilibrium water content after 5 min >85%). The MMW-CH compartment degraded more slowly and provided significantly more resistance to compression (28% ± 1% of weight loss at 4 wk; compression modulus HA = 18 ± 6 kPa) than the LMW-CH compartment (34% ± 1%; 7.7 ± 0.8 kPa) as required to match the physiologic healing rates of bone and gingiva and their mechanical properties. More than 90% of all human primary periodontal cell populations tested on the corresponding compartment survived during cytocompatibility tests, showing active cell metabolism in the alkaline phosphatase and collagen deposition assays. In vivo tests showed high biocompatibility in wild-type mice, tissue ingrowth, and vascularization within the scaffold. Using the periodontal ectopic model in nude mice, we preseeded scaffold compartments with human gingival fibroblasts, osteoblasts, and PDL fibroblasts and found a dense mineralized matrix within the MMW-CH region, with weakly mineralized deposits at the dentin interface. Together, these results support this resorbable trilayer scaffold as a promising candidate for periodontal regeneration.